Requirements for ingestion of Chlamydia psittaci by mouse fibroblasts (L cells). - Byrne, G I (1976)
Ingestion of 14C-amino acid-labeled Chlamydia psittaci (6BC) by mouse fibroblasts (L cells) was inhibited when the host cells were incubated for 30 min at 37 degrees C in Earle salts containing 10 mug of crystalline trypsin per ml. Tryptic digestion also inhibited the ingestion of 1-mum polystrene latex beads. Trypsin-treated L cells almost completely recovered their ability to ingest chlamydiae after 4 h at 37 degrees C in medium 199 with 5% fetal calf serum. Cycloheximide (10 mug/ml) blocked this recovery. Heating 14C-amino acid-labeled C. psittaci for 3 min at 60 degrees C inhibited its ingestion by L cells, whereas inactivating it with ultraviolet light was without effect on the ingestion rate. These results show that efficient ingestion of C. psittaci by L cells involves trypsin-labile sites on the host and heat-sensitive sites on the parasite. The failure of excess unlabeled infectious C. psittaci to promote the ingestion of 14C-labeled heat-inactivated chlamydiae suggests that direct interaction between these two sites must occur for uptake to proceed normally.